Health care expenditure and maternal mortality in Africa (2021)
Maternal Health has continued to generate some serious concerns across the world, especially in the area of child delivery and the associated complications which largely account for several maternal deaths in most developing countries. The study, therefore, assessed the combined impact of Healthcare expenditure, access to safe drinking water and sanitation Services on maternal mortality in selected 30 African countries spanning 2000-2017. The retrospective design was adopted to examine the statistical associations between the dependent and the independent variables of the study. In the panel regression model analysis, the robust fixed effect estimator was preferred to the random effect model as was determined by the result of the Hausman test. The findings from this study showed that out-of-pocket expenditure had a 0.09percent significant effect on maternal mortality in the robust fixed-effect model. Also, the domestic government general Health expenditure had a 0.05 percent significant effect on maternal mortality in the region. Moreover, access to basic drinking water Services exerted a significant negative effect (-0.01) on the maternal mortality ratio in the selected countries. However, access to at least basic sanitation Services had no significant effect on maternal mortality. Therefore, the authors concluded that a multi-sectorial approach was required to tackle maternal mortality by paying attention to some health- related sectors like water and sanitation Services.